The Influence of Competence, Motivation, and Compensation on Civil Servants' Performance at the Mentawai Islands Port Office - ., Nazarwin (Journal of Ecohumanism, 2024)
This study examines the impact of competence, motivation, and compensation on the performance of civil servants at the Mentawai Islands Port Office. Aimed at contributing to the limited body of research on public sector performance in Indonesia’s remote regions, this research explores how these factors influence employee performance in a public service context. Data were collected from all 70 civil servants across three main port offices in the Mentawai Islands using structured questionnaires. The analysis, conducted using SPSS 26.0 and employing multiple regression techniques, reveals that motivation is the most significant predictor of performance, followed by compensation and competence, with coefficients of 0.659, 0.292, and 0.135, respectively. The regression equation highlights motivation as the primary driver of employee performance, suggesting that public sector organizations in remote areas must prioritize motivational strategies along with adequate compensation and skill development to enhance service delivery. These findings provide actionable insights for policymakers and public administration leaders aiming to boost civil servant performance through targeted human resource practices. By creating a motivating environment, ensuring fair compensation, and fostering necessary competencies, organizations can achieve higher employee performance and ultimately improve public service quality in outlying regions.